Mode of Application of Peracetic Acid-Based Disinfectants has a Minimal Influence on the Antioxidant Defences and Mucosal Structures of Atlantic Salmon (Salmo salar) Parr - Carletto, Danilo; Furtado, Francisco; Zhang, Junjie; Asimakopoulos, Alexandros G.; Eggen, Maia; Verstege, Gerhardus C.; Faggio, Caterina; Mota, Vasco C.; Lazado, Carlo C. (Frontiers in Physiology, 2022)
Peracetic acid (PAA) is an oxidative disinfectant with a broad spectrum of antimicrobial activity and low environmental impact. In this study, we investigated the physiological impacts of PAA application in Atlantic salmon (Salmo salar) parr reared in freshwater recirculating aquaculture systems over a 4-week period. PAA at a target concentration of 1 mg/L was administered either in pulse (every 3 days) or continuous. The group that did not receive PAA served as a control. Tissue samples were collected for histology, gene expression, and biochemical analyses at day 0 and after 2 and 4 weeks of exposure. The expression of genes encoding for antioxidant defense in the olfactory organs, skin, and gills changed during the trial, but the temporal effects were more pronounced than inter-treatment impacts. The glutathione group of antioxidant genes was more responsive to PAA. In most cases, an upregulation was observed. Significantly lower levels of reactive oxygen species were identified in the plasma and skin mucus of the two PAA-exposed groups at week 4; nonetheless, significantly increased levels of total antioxidant capacity were only observed in the skin mucus of the continuous treatment group. Additional markers of oxidative stress (i.e., 8-oxo-2'-deoxyguanosine and o,o'-dityrosine) were analysed in the skin, gills, liver, and dorsal fins. These markers were unaffected by the two PAA treatments. Sporadic reversible structural alterations were observed in the three mucosal organs; the changes were time-dependent, and the effects of PAA treatment were minimal. The number of mucous cells varied over time but not within treatments except in the skin of the pulse group at week 4 where a reduction was observed. The ratio of acidic and neutral mucous cells in the skin and gills were affected by PAA treatments especially in the pulse group. Overall, this study revealed that Atlantic salmon parr mobilised mucosal and systemic antioxidant defences against the oxidative disinfectant PAA, but it was evident that the mode of application did not impose a strong influence. The minimal effects of PAA application on the indicators of health and welfare underscore the potential use of PAA as a routine disinfectant in recirculating aquaculture systems.